MCMSL Translator: Malaysian Text Translator for Manually Coded Malay Sign Language - Mazlina, Abdul Majid; Masrulehsan, Mamat; Ruzaini, Abdullah Arshah (2014)
Sign Language forms the natural way of communication for hearing-impaired people just like speech for vocal people. In Malaysia, Manually Coded Malay Sign Language (MCMSL) is only sign language recognizes by Ministry of Education to use in teaching and learning, while Malaysian Sign Language (MSL) is the widely used by the hearing-impaired community for communication. In school, current teaching and learning of sign language used a traditional method i.e. flash card, picture etc has made student less interested to learn sign language. Therefore, there is an increasing need to develop multimedia applications that are capable to translate from Malaysian Text to MCMSL and helps students to learn sign language effectively and fun. Thus, this project focused on developing the multimedia application called MCMSL Translator based on Mayer’s Cognitive Theory of Multimedia Learning (Mayer’s CTML), including a video database of MCMSL for primary school. The qualitative approach such as questionnaire, observation and interview will conducted with teachers, students and parents to analyze student performance when using MCMSL Translator.